If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + -13 = 6x + 95 Reorder the terms: -13 + 15x = 6x + 95 Reorder the terms: -13 + 15x = 95 + 6x Solving -13 + 15x = 95 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -13 + 15x + -6x = 95 + 6x + -6x Combine like terms: 15x + -6x = 9x -13 + 9x = 95 + 6x + -6x Combine like terms: 6x + -6x = 0 -13 + 9x = 95 + 0 -13 + 9x = 95 Add '13' to each side of the equation. -13 + 13 + 9x = 95 + 13 Combine like terms: -13 + 13 = 0 0 + 9x = 95 + 13 9x = 95 + 13 Combine like terms: 95 + 13 = 108 9x = 108 Divide each side by '9'. x = 12 Simplifying x = 12
| 133-y=180 | | (x-8)(3x-7)=0 | | 15x-2y=4y | | 30+x+33=90 | | 7(x+2)=-4x+25 | | 8+3x=3x-8 | | (2t-4)(t+3)=0 | | y=2x+39 | | 4x+48+7x=15 | | -3(b+8)=9 | | j/5=12 | | 16x-36=180 | | SinW=0.76 | | 4r+2=r+5 | | (a+3)(a+5)=0 | | (2x-30)=40 | | 4x+6-7(x+1)=5x+2 | | C=25m+75 | | (2xy)(2xy)(2xy)= | | 64q^2-16=0 | | 100=20*10 | | 0.5(8x+4)=3(4x+8) | | -15(x-4)=-2 | | -82=5p+8 | | 2x^3+(-3k+3)x+(3k+5)=0 | | 6(2x+4)=(4x+8) | | 0.005x+-0.03=0.01 | | 2x-3y+z=-24 | | 170=x^2 | | 6=-n+1 | | 6x-13=68 | | (2x)-(x)= |